A VARIAÇÃO LINGUÍSTICA E O PORTUGUÊS DO BRASIL: Uma análise sobre o idioma, a elite e o (des)respeito - AGUIAR, Hugo Leonardo Lima de (2024)
This study analyzes the relationship between language, the elite, and linguistic disrespect, focusing on the linguistic varieties present in Brazilian Portuguese. The research seeks to understand how linguistic variation relates to practices of social disrespect, highlighting the importance of linguistic diversity as a fundamental element in fostering interaction and coexistence among different forms of expression. Furthermore, it underscores the role of power dynamics in the hierarchization of these varieties, which are often marginalized in educational, media, and social contexts. The analysis emphasizes the need to recognize and value linguistic plurality, promoting practices that combat linguistic prejudice and encourage a more inclusive society. The research, qualitative and cross-sectional in nature, classified as basic and exploratory, utilized a bibliographic study with an analytical approach, grounded in renowned Sociolinguistics scholars such as Labov (1983), Bagno (2003), and Alkmim (2001), to discuss linguistic variation, its social implications, and linguistic prejudice. Although this topic is under discussion in academia, it is essential to encourage its broader dissemination, delving deeper through other studies that make it more accessible to non-academic audiences. Reducing linguistic disrespect, often concealed and perpetuated especially by the dominant classes, is imperative. This study is significant as it addresses the importance of linguistic respect in society, emphasizing the need for understanding and valuing diverse forms of expression, while contributing to the promotion of educational, cultural, and social diversity.